Círculo de leitura no ensino médio:uma análise a partir da estética da recepção - Silva, Elza Sueli Lima (2019)
This study was born from the teaching experience, from which it is possible to realize the insufficiency of the historiographic and structural literature teaching in the context of the Basic Education. Centered on the formation of the literature reader, it aims to understand the receiving of the literary text of students of the 3rd year of high school, through reading workshops, based on the methodology of the Reading Circles, guided mainly by theoretical and methodological thoughts of Cosson (2016, 2017) and Yunes (1995, 1999, 2002, 2014). It is a qualitative research that, besides the application of reading workshops, used the following tools and procedures for data collection: participant observation, narrative interview, field diary and observations of the readings performed by students at school, when they did not follow the school routine. The data generated from them were analyzed in the light of the postulates of Aestheticsof Reception and History of Reading defended by Chartier (1996, 1998, 1999) and Jauss (1979, 1994), in dialogic with others authors. Therefore, empirical reality has shown that most of the students are readers of “non-school” literature and have different ways of reading and take ownership of the senses of the text. While the minority of the readers of classical literature reads the works, updating them, according to their cultural repertoire and the historical time in which they are inserted. Classmates, friends and the virtual world had influence in the formation of these readers. Finally, the research indicates that in order to form readers in the formal educational space it is necessary to establish a culture of reading, promoting the free literary reading as a gateway to other more complex readers' experiences, provided in Reading Circles